Novel SO2 spectral evaluation scheme using the 360-390 nm wavelength range - Bobrowski, Nicole; Kern, Christoph; Platt, Ulrich; Hörmann, Christoph; Wagner, Thomas (Atmospheric measurement techniques, 2010)
Differential Optical Absorption Spectroscopy (DOAS) is a well established spectroscopic method to determine trace gases in the atmosphere. During the last decade, passive DOAS, which uses solar radiation scattered in the atmosphere as a light source, has become a standard tool to determine SO2 column densities and emission fluxes from volcanoes and other large sources by ground based as well as satellite measurements. For the determination of SO2 column densities, the structured absorption of the molecule in the 300-330 nm region (due to the A1B1 ← X1A1 transition) is used. However, there are several problems limiting the accuracy of the technique in this particular application. Here we propose to use an alternative wavelength region (360-390 nm) due to the spin-forbidden a3B2 ← X1A1 transition for the DOAS evaluation of SO2 in conditions where high SO2 column densities prevail. We show this range to have considerable advantages in such cases, in particular when the particle content of the plume is high and when measurements are performed at large distances from the area of interest.